The essential guide to doing your research project - O'Leary, Zina (SAGE, 2014)
The Essential Guide to Doing Your Research Project 2e is the ultimate companion to successfully completing your research project. Warm and pragmatic, it gives you the skills and the confidence needed to succeed no matter what happens along the way. The book guides you through every step of your research project, from getting started to analysing data and writing up. Each stage is clearly set out, highlighting best practice and providing practical tips and down-to-earth advice for actually doing research.